2018
DOI: 10.1186/s13568-018-0606-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bacillus subtilis lipopeptides in anti-cancer I: induction of apoptosis and paraptosis and inhibition of autophagy in K562 cells

Abstract: The lipopeptide iturin from Bacillus subtilis has been found to have a potential inhibitory effect on breast cancer, alveolar adenocarcinoma, renal carcinoma, and colon adenocarcinoma. In this study, the potential of B. subtilis lipopeptides (a mixture of iturin homologues, concentration of 42.75%) to inhibit chronic myelogenous leukemia was evaluated using K562 myelogenous leukemia cells. The results showed that the lipopeptides could completely inhibit the growth of K562 at 100 μM, with an IC50 value of 65.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 43 publications
1
35
0
1
Order By: Relevance
“…This hypothesis was verified by protein expression of caspase-3 and cleaved caspase-3 protein ( Figures 5E, F ). The increased expression of cleaved caspase-3 represents activation of effector caspases, indicating apoptosis ( Zhao H. et al., 2018 ). We showed that Pb exposure caused obvious apoptosis of HEK-293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was verified by protein expression of caspase-3 and cleaved caspase-3 protein ( Figures 5E, F ). The increased expression of cleaved caspase-3 represents activation of effector caspases, indicating apoptosis ( Zhao H. et al., 2018 ). We showed that Pb exposure caused obvious apoptosis of HEK-293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The LPs are composed of a peptide and a fatty acid chain and have been shown to exhibit antitumour activity in vitro (Zhao et al . ). Reports on the Bacillus LPs, namely SUR, Iturin and Fengycin, suggest that they possess antitumour activities.…”
Section: Anticancer Potential Of Biosurfactantsmentioning
confidence: 97%
“…Recently, Zhao et al . () showed the B. subtilis LPs consisting of a majority of iturin exhibited promising potential in inhibiting chronic myelogenous leukaemia in vitro via simultaneously causing paraptosis, apoptosis and inhibition of autophagy. The anticancer mechanisms of Bacillus LPs have been extensively studied and SUR has been found to display an antiproliferative effect via apoptosis induction, cell cycle arrest and survival signalling suppression.…”
Section: Anticancer Potential Of Biosurfactantsmentioning
confidence: 99%
“…The intrinsic pathway is indicated by the expression of caspase-3, caspase-9, BCl-2 and BAX, while, the extrinsic pathway is marked by the expression of caspase-8 and caspase-10. Among caspases, the caspase-8, caspase-9 and caspase-10 are initiators that are activated via binding to specific proteins; while caspase-3 is an effector caspase that is eventually activated by the active initiator caspases through photolytic cleavage [102,103]. Activation of Caspase-3 is often the indicator to confirm that the cancer cells have been subjected to cell shrinkage, nuclear fragmentation and chromatin condensation without affecting surrounding healthy tissues [104].…”
Section: Anticancer Activitymentioning
confidence: 99%